Behavioral changes after hospital discharge in preschool children experiencing emergence delirium after general anesthesia: A prospective observational study. Issue 10 (6th August 2021) - Kim, Jonghae; Byun, Sung Hye; Kim, Jun Won; Kim, Ji‐Yoon; Kim, Yun Jin; Choi, Nayeon; Lee, Bong Soo; Yu, Seungcheol; Kim, Eugene
Abstract: Background: Emergence delirium is well known as early postoperative behavioral change after general anesthesia. However, it is unclear whether children with emergence delirium have negative behavioral changes after hospital discharge. Aim: This observational study investigated the association between emergence delirium and posthospital behavioral changes. Methods: One‐hundred preschoolers aged 2–7 years undergoing elective surgery were enrolled in 2 tertiary university hospitals. Preoperative anxiety level was assessed using modified Yale preoperative anxiety scale. Emergence delirium was defined via pediatric anesthesia emergence delirium score ≥12 at any time in the recovery room. We divided the delirium score into a delirium‐specific score (the sum of the first 3 items: eye contact, purposeful movement, and awareness of surrounding) and a pain‐related score (the sum of the last 2 items: restlessness and inconsolability). High delirium scores represent severe emergence delirium. Posthospital behavioral changes were assessed by a change in Child Behavior Checklist 1.5–5 scores before and 1 week after surgery. The primary outcome was the total behavior checklist scores 1 week after surgery. Multiple linear regression was performed to identify risk factors for posthospital behavioral changes. Results: Children with emergence delirium ( n = 58) had higher postoperative behavior checklist scores than children without emergence delirium ( n = 42) [mean (SD), 22.8 (17.5) vs. 14.0 (12.1); mean difference (95% CI), 8.8 (1.5–16.2)]. Increases in preoperative anxiety level [regression coefficient (b) (95% CI) =0.241 (0.126–0.356)] and peak delirium‐specific score [b = 0.789 (0.137–1.442)] were associated with an increase in behavior checklist score 1 week after surgery, while pain‐related score, type of surgery, premedication, and age were not. Conclusion: Children with emergence delirium developed more severe behavior changes 1 week after surgery than those without emergence delirium. High preoperative anxiety level and emergence delirium scores were associated with posthospital behavioral changes.